Attitudes, awareness, and roles of parents in children’s musical instrument learning at The Klang Valley music centre - Chang, Lok Yew; Ang, Mei Foong (Human Resource Management Academic Research Society, 2021)
Parents always play a pivotal role in children’s musical development. This study investigated parental attitudes and awareness of parental roles in children’s music learning. Ten parents in Kuala Lumpur who have been sending their children (7-12 years old) to learn musical instrument in a music centre participated in this research. The data were collected through a set of interview question based on Youm’s parental attitude framework (2013). The findings revealed that the parents in Klang Valley, Malaysia have clear goals for their children through music learning but lack the initiative and confidence to guide their children when they are practising at home; local parents emphasized the training of independence and responsibility for their children by providing minimal assistance. Although they were aware that parental roles are important, they showed a low willingness to guide their children at home, as well as low willingness on expanding musical knowledge, and a low motivation to enrich and perform their roles.